Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam dalam Mengembangkan Kreativitas Peserta Didik di SMP Negeri 1 Leuwiliang Kabupaten Bogor - Ujang Supriadi; Riyanto; Yusi Srihartini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of the independent curriculum is a concept that is preferred in the world of education because it requires educators to show creativity in the learning process while allowing students to explore their potential and foster creativity, innovation, and independence. As with the new discourse, there are of course pros and cons to consider. Education serves as a means to form and achieve personal goals. Educational guidance must be derived from the Qur'an, because the Qur'an consistently provides instructional cues as a whole, from the opening verse to the closing verse. Through obedience to the values embraced in the Qur'an, individuals can be guided towards creativity, dynamism, and the achievement of the essential values of ubudiyah in relation to their creator. This research is a descriptive qualitativeresearch. Data collection techniques use observation, interviews, and documentation. The data obtained was analyzed using three stages, namely: 1) Data reduction, 2) Data presentation, 3) Drawing conclusions and verification. The data validity techniques used were: The sources observed were, Islamic Religious Education Teachers, Principals, Curriculum Officers, and Students at SMPN 1 Leuwiliang, Bogor Regency. The results of this study show that the implementation of the learning process of the application of the independent curriculum in Islamic Religious Education at SMPN 1 Leuwiliang, Bogor Regency has been carried out through the implementation of summative assessments at the end of the odd semester of the 2023/2024 school year. These assessments combine different approaches, starting with face-to-face teaching during the post-pandemic era.several learning models are introduced, project-based learning models, problem-based learning models, discovery learning models, and inquiry learning. The application of differentiated learning as a form of independent curriculum has resulted in a positive transformation in the development of student learning creativity in Islamic religious education at SMPN 1 Leuwiliang, Bogor Regency. This is evidenced by the increase in students' abilities after the implementation of independent learning. critical thinking skills, emotional sensitivity, facilitating collaborative efforts in the completion of academic tasks, encouraging the dissemination of their work in social circles.